Microbiology of septic arthritis in young Auckland children. (31st August 2021) - van den Boom, Mirjam; Lennon, Diana R; Crawford, Haemish; Freeman, Joshua; Castle, Jennifer; Mistry, Raakhi; Webb, Rachel
Abstract : Background: Kingella kingae is an important cause of septic arthritis in young children, with modern laboratory methods leading to increased detection. Prevalence of this pathogen in New Zealand, where there are high rates of childhood infections due to Staphylococcus aureus and Streptococcus pyogenes, is not known. Methods: We conducted a retrospective review of children <5 years with septic arthritis (without osteomyelitis) at a tertiary children's hospital in Auckland, over 10 years (2005–2014). Data were collected on demographics, microbiology, clinical presentation, investigations and management. Results: Of the 68 cases of septic arthritis, 57 (83.8%) occurred in children aged <24 months. Among those <3 months, Streptococcus agalactiae (Group B streptococcus) was predominant (45.5% of 11 cases), followed by S. aureus (36.4%). The most common pathogen in those 3 to <12 months was Streptococcus pneumoniae (38.5% of 13 cases). In children aged 12 to <24 months, K. kingae was most common (30.3% of 33 cases). Of the 12 cases of K. kingae, 91.7% were identified from synovial fluid culture. All K. kingae isolates were susceptible to amoxicillin. Conclusions: K. kingae is the leading pathogen in septic arthritis in New Zealand children aged 12 to <24 months. Routine inoculation of synovial fluid into blood culture bottles at time of sample collection, in addition to use of polymerase chain reaction methods, should be encouraged to improve detection rates. For infants and preschool children presenting with single joint septic arthritis, empiric antibiotics should include cover for S. aureus and K. kingae .